The Analysis Relates to the Impact Caused by the Capital Adequacy Ratio and Loan to Deposits Ratio Which Mediated by Return on Assets Towards the Stock Prices - Marettos Hutabarat, Lissom; Esti Riwayati, Hedwigis (Dinasti Publisher, 2021)
The research purpose was to discover and analyze the role of the Capital adequacy ratio and loan to deposits ratio towards Stock prices which are mediated by return on assets. The population in this research were 4 (four) state-owned banks and the sample process through purposive sampling technique with the total number of elements in the population was a sample whose subjects had met the required criteria. The research data was obtained through the publication of Financial Services Authority related to the financial statements of conventional banks and the yahoo finance website. The analysis technique used was panel data regression and data processing through Microsoft Excel 2020 and Eviews 10 applications. The results show that the Capital adequacy ratio had a positive and significant impact on stock prices, loan to deposits ratio and return on assets have no effect on stock prices. The Capital adequacy ratio had a negative and significant impact towards return on assets, loan to deposits ratio had no impact towards return on assets, return on assets is able to partially mediate the impact from Capital adequacy ratio towards stock prices and return on assets is unable to mediate the impact from loan to deposits ratio towards stock prices of state-owned banks in Indonesia during this research period.